Association of Anemia and Blood Group among Vegetarian and Non-Vegetarian Students of University Campus, Rajarshi Janak University, Janakpurdham, Nepal - Jha, Uday Kant; Patel, Amit Kumar; Chaurasiya, Aanand Kumar; Pandey, Rajiv Kumar; Pajiyar, Ajit; Shah, Abhinash; Sharma, Sunil Kumar; Karn, Abhisekh Lal; Mukhiya, Naresh Kumar; Mandal, Rekha; et al. (Med Phoenix, 2025)
Introduction: Anemia is the major health problem among the young adults. Its prevalence increases among young adults whose diet doesn’t contain non-vegetarian food is at high risk of getting anemic. Vegetarians are more vulnerable to be anemic whose diet doesn’t contain vit-B12, folic acid and iron supplements. .The prevalence of anemia among students will help identify association between blood groups and vegetarian/non-vegetarian diet in the university campus, Rajarshi Janak University, Janakpurdham. Materials and Methods: It was a cross-sectional study conducted at the University Campus, Rajarshi Janak University, Nepal Janakpurdham, Nepal. The measurement of Hemoglobin (Hb) was done by Cyanmethemoglobin method Recommended by ICSH and the blood group ABO with RH system was performed by slide agglutination method. Results: Out of 130 students 51(39.24%) were the prevalence of anemia among young adults. Status of anemia by blood group (n=130) shows that the Blood Group AB has the highest prevalence of anemia, followed by Blood Group O, followed by Blood Group A, and least in B. The association between anemia and blood group was found significant (p=0.050). Among non-vegetarian students38.4% were anemic whereas 60% of vegetarian students were anemic. The association between dietary habits and the anemia was found insignificant (p=0.332). Conclusion: According to this study, it can be concluded that the anemia was more common among female students, it may a reason for concern because the cause could be due to poor dietary habits or a reduction in food facilities.